ADOPSI INOVASI PETANI KELAPA SAWIT TERHADAP SISTEM INTEGRASI SAPI – KELAPA SAWIT (SISKA) DI KABUPATEN KAMPAR - Joko Prestiwo; Susy Edwina; Evy Maharani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This study aims to determine the adoption innovation and to know the level of adoption innovation of palm farmer for the Integration Systems of Palm Oil Cattle Programs (SISKA) in Kampar. The data collection method using survey methods. The population in this study were farmers who applied SISKA’s program and farmers who no longer apply SISKA’s program. The samples of this technique are 31 persons, including respondents who applied and had not apply SISKA’s program. Analysis data used descriptive method. Variable characteristics of farmers and adoption of innovation analyzed using Likert Scale. The results showed that the Innovation Adoption Program (SISKA) by knowledge stages in average category, persuasion stage in average category, decision stage divided into two parts, the decision adopting included in low category, decision not to adopting included in average category. Implementation stage classified in very low category and at the confirmation stage in very low category. The level of innovation adoption by the farmers against SISKA program in Kampar obtained with low category.     Keywords: Adoption, Innovation, Integration, Farmers